The relationship between needle sugar carbon isotope ratios and tree rings of larch in Siberia - Rinne, K. T.; Saurer, M.; Kirdyanov, A. V.; Loader, N. J.; Bryukhanova, M. V.; Werner, R. A.; Siegwolf, R. T. W.
Significant gaps still exist in our knowledge about post-photosynthetic leaf level and downstream metabolic processes and isotopic fractionations. This includes their impact on the isotopic climate signal stored in the carbon isotope composition (delta C-13) of leaf assimilates and tree rings. For the first time, we compared the seasonal delta C-13 variability of leaf sucrose with intra-annual, high-resolution delta C-13 signature of tree rings from larch (Larix gmelinii Rupr.). The trees were growing at two sites in the continuous permafrost zone of Siberia with different growth conditions. Our results indicate very similar low-frequency intra-seasonal trends of the sucrose and tree ring delta C-13 records with little or no indication for the use of 'old' photosynthates formed during the previous year(s). The comparison of leaf sucrose delta C-13 values with that in other leaf sugars and in tree rings elucidates the cause for the reported C-13-enrichment of sink organs compared with leaves. We observed that while the average delta C-13 of all needle sugars was 1.2% more negative than delta C-13 value of wood, the delta C-13 value of the transport sugar sucrose was on an average 1.0% more positive than that of wood. Our study shows a high potential of the combined use of compound-specific isotope analysis of sugars (leaf and phloem) with intra-annual tree ring delta C-13 measurements for deepening our understanding about the mechanisms controlling the isotope variability in tree rings under different environmental conditions. 2015